Binary Tree Blockchain of Decomposed Transactions - Davut Çulha (Journal of Universal Computer Science)
Widespread adoption of blockchain technologies requires scalability. To achieve scalability, various methods are applied, including new consensus algorithms, directed acyclic graph solutions, sharding solutions, and off-chain solutions. Sharding solutions are particularly promising as they distribute workload across different parts of the blockchain network. Similarly, directed acyclic graphs use graph data structures to distribute workload effectively. In this work, a binary tree data structure is used to enhance blockchain scalability. Binary trees offer several advantages, such as the ability to address nodes with binary numbers, providing a straightforward and efficient method for identifying and locating nodes. Each node in the tree contains a block of transactions, which allows for transactions to be directed to specific paths within the tree. This directionality not only increases scalability by enabling parallel processing of transactions but also ensures that the blockchain can handle a higher volume of transactions without becoming congested. Moreover, transactions are decomposed into transaction elements, improving the immutability of the binary tree blockchain. This novel decomposition process helps to minimize the computational overhead required for calculating account balances, making the system more efficient. By breaking down transactions into their fundamental components, the system can process and verify transactions more rapidly and accurately. This approach effectively realizes implicit sharding using a binary tree structure, distributing the processing load more evenly and reducing bottlenecks. The proposed method is simulated to assess its performance. Experimental results demonstrate the method's scalability, showing that it can handle a significantly higher transaction throughput compared to traditional blockchain structures.